A comparison of the treatment recommendations for neurogenic lower urinary tract dysfunction in the national institute for health and care excellence, European Association of Urology and international consultations on incontinence guidelines. Issue 7 (17th April 2018) - Jaggi, Ashley; Drake, Marcus; Siddiqui, Emad; Fatoye, Francis
Abstract : Aims: Healthcare guidelines are an important vehicle in establishing up‐to‐date evidence based medicine (EBM) in clinical practice. Due to varying development processes, clinical guidelines created by different institutions can often contain contrasting recommendations. This can have implications for optimal and standardized patient care across management settings. Methods: The similarities and differences of treatment recommendations made in the National Institute for Health and Care Excellence (NICE), The European Association of Urology (EAU), and the International Consultation on Continence (ICI) guidelines for neurogenic lower urinary tract dysfunction (NLUTD) were assessed. Results: The guidelines generally agree on their approach to conservative management, including behavioral therapies, and catheterization techniques. There was discrepancy on the benefit of using an alpha blocker in NLUTD and bladder outlet obstruction (BOO) and administering Botulinum toxin A (Onabotulinum‐A) in NLUTD. The highest degree of divergence was seen in recommendations for surgical treatments, where the EAU made gender‐specific recommendations, and gave continent urinary diversion higher preference than given in the NICE and ICI guidelines. Conclusions: In the absence of high‐quality clinical evidence, many of the recommendations made across all three guidelines are based on expert opinion. NICE, the EAU and ICI have similarities but they place differing emphasis on costs and expert opinion, which translated in notably different recommendations. It is evident that increased research efforts, possibly in the form of prospective registries, pragmatic trials, and resource utilization studies are necessary to improve the underlying evidence base for NLUTD, and subsequently the strength and concordance of recommendations across guidelines.